Plant sciences, public policies and food security - Zeigler, Robert S. (SAGE Publications, 2019)
Food security was a major global concern in the second half of the 20th century. A positive feedback loop between public policy and technological innovation created abundant food supplies that averted predictions of famine and social chaos. Following the successful global effort to combat hunger, policy attention turned to problems of the environmental footprint of agriculture and other nutrition and diet-related health problems. Policies are developed in response to challenges presented by technology-induced change. As the rate of technological change accelerates, policy makers struggle to keep up and policies risk becoming irrelevant or stymying positive impact of innovation. Public or philanthropic investments created the foundation for private investment in technologies that have been widely adopted. As the public sector reduces its investments in research and development, it is not clear that the private sector has the appetite or means to make the needed investments. Examples of challenges facing agriculture and food security include access to and use of genetic resources, genetically modified crops and the global community’s ability to respond to and mitigate human-induced climate change. Proposed solutions to the world’s many serious challenges almost invariably involve some kind of coordinated and coherent multilateral institutional actions. Yet, today, global political trends appear to be shifting to more unilateral, bilateral and nationalistic perspectives hampering our capacity to respond effectively.